IMPROVING STUDENTS' INTERACTION IN SPEAKING CLASS THROUGH INFORMATION GAP ACTIVITIES - Andri Defrioka (University of Muhammadiyah Purwokerto, 2009)
The problem dealt with a passive class, where students did not response and avoided interaction with teacher and other students, were tried to be solved. The purpose of the research was to test to what extend the applying information gap activities could improve students’ interaction in speaking class. Classroom action research procedures (plan, act, observe and reflection) were used to study the process and participant out comes. The participants of this research were the third year students of Building Department of SMKN 1 Padang, consisted of 22 students. One of the English teachers took part in the research as collaborator to assist the implementation of information gap activities and to observe the out comes. The research was conducted in two cycles with four meetings for each. The information gap activities were applied at each meeting with different topic of the lesson. In the first cycle, not all of students interacted with the teacher and other friends. Only some of them participated in the class. After analyzing the activities in the first cycle, the cycle II followed there reflection on the first cycle to further develop materials, activities. The result of the research indicated that the implementation of information gap activities can better improve the students’ interaction in speaking class. Student-centered class included pair work and group work also contributed to improve out comes .Besides, students were active to interact with their teacher and other students. The students participated at all activities. Finally, the classroom action research process itself helped students and teacher reflects on their successes and failures in teaching and learning process.